(untitled) (Journal of the College of Basic Education, 2026)
This study aimed to evaluate the impact of implementing a small digital projects strategy on the development of academic entrepreneurship skills among students in the faculties of education at the Universities of Baghdad and Kufa. The study adopted an analytical and descriptive approach, using a specially designed questionnaire as the main tool for collecting data from a sample of 400 male and female students. The data was analysed quantitatively in depth, with statistical analysis including the calculation of arithmetic means and standard deviations, as well as the exploration of correlational relationships using Pearson and Spearman coefficients. The study went beyond traditional analysis, incorporating innovative indicators to assess qualitative aspects such as the readiness of initial digital models and the entrepreneurial flexibility of students. The study found that there is a significant positive impact of the micro-digital entrepreneurship strategy on enhancing academic entrepreneurship skills, particularly in vital areas such as teamwork, creative thinking, and identifying innovative business opportunities. The results also highlighted strong and significant statistical correlations between students’ exposure to this strategy and the level of development of their entrepreneurial skills, confirming the pivotal role of academic and institutional support and encouragement. However, the study revealed challenges in some practical aspects, such as the effectiveness of digital marketing, building specialized professional networks, and students’ ability to attract investment for their start-up projects. Based on these findings, the study recommends the development of integrated training programmes focusing on advanced practical skills, the strengthening of partnerships between universities and external institutions, and the activation of project incubation mechanisms to support students in their academic entrepreneurial journey.